Molecular Characterization of a Novel Cathepsin L in Macrobrachium nipponense and Its Function in Ovary Maturation - Jiang, Sufei; Xiong, Yiwei; Zhang, Wenyi; Zhu, Junpeng; Cheng, Dan; Gong, Yongsheng; Wu, Yan; Qiao, Hui; Fu, Hongtuo (Frontiers in Endocrinology, 2022)
Cathepsin L genes, which belonged to cysteine proteases, were a series of multifunctional protease and played important roles in a lot of pathological and physiological processes. In this study, we analyzed the characteristics a cathepsin L (named Mn-CL2) in the female oriental river prawn, Macrobrachium nipponense which was involved in ovary maturation. The Mn-CL2 was1,582 bp in length, including a 978 bp open reading frame that encoded 326 amino acids. The Mn-CL2 was classified into the cathepsin L group by phylogenetic analysis. Real-time PCR (qPCR) analysis indicated that Mn-CL2 was highly expressed in the hepatopancreas and ovaries of female prawns. During the different ovarian stages, Mn-CL2 expression in the hepatopancreas and ovaries peaked before ovarian maturation. In situ hybridization studies revealed that Mn-CL2 was localized in the oocyte of the ovary. Injection of Mn-CL2 dsRNA significantly reduced the expression of vitellogenin. Changes in the gonad somatic index also confirmed the inhibitory effects of Mn-CL2 dsRNA on ovary maturation. These results suggest that Mn-CL2 has a key role in promoting ovary maturation.